Our Authorial Authority - Paine, Robert (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1989)
This article moves from Sir James Frazer, through successive generations (British for the most part) of social anthropologists, and onto the post-modern present-day of James Clifford and Marilyn Strathern, among others, and to the place that an advocacy anthropology may have in it. It enquires, in each case, about (i) the nature of the “authority” which the anthropologist appropriates and (ii) strategies used to persuade and/or assuage readers of anthropology (among whom are included its subjects). It is, then, a commentary on the kind of issues brought to us most notably in Writing Culture (eds. Clifford and Marcus, 1986) and, in particular, on some changes in the presentation of the anthropological “self.”